A study of emotional intelligence between inter university and inter collegiate hockey players / Zamirullah Khan … [et al.] - Khan, Zamirullah; Haider, Zeeshan; Ahmed, Naseem; Khan, Sartaj (Faculty of Sports Science and Recreation, 2013)
Emotions play a central role in sports performance. Sport is an emotional experience for many athletes. Emotional intelligence is the ability, capacity, skill, or self-perceived ability to identify, assess, and manage the emotions of one’s self and of others. People who possess a high degree of emotional intelligence know themselves very well and are also able to sense the emotions of others. Emotional intelligence is emerging as the most important and effective personal skill of the new century. The current study is an attempt to examine the difference of emotional intelligence between interuniversity and intercollegiate hockey players. Mangal Emotional Intelligence Inventory (MEII) was applied for the collection of the data from the hockey players. The age ranged between 16 to 23 years. The results of the study indicated that interuniversity players are more emotionally intelligent than the intercollegiate players.